Influence of Structural, Thermoelectric Power and Catalytic Efficiency of Nd-Doped Mn3O4 - Geetha, V.T.; Puthilibai, G.; Induja, S. (Asian Journal of Chemistry, 2019)
Hexagonal shape Nd doped Mn3O4 samples were prepared via microwave route using urea as reducing agent. Nd doped Mn3O4 magnetic, structural, optical and morphological properties of the synthesized hexagonal like particles were examined by diffused reflectance spectroscopy (DRS) and photoluminescence (PL), XRD, SEM, TEM and vibrating sample measurements (VSM) studies. Morphological results showed the hexagonal shape morphology and uniform size dispersal. The crystallite size and the particle size calculated and the TEM monographs designate the correlation of the data obtained from both measurements. It could be noted that saturation magnetization (Ms) and remanence (Mr) values reduce by maximizing neodymium replacement.